KAJIAN TENTANG APLIKASI MOBILE INTERFACE PENCARIAN CITRA PADA BASIS DATA ONLINE BERBASIS iOS - Daniel Antineus; Lina Lina; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The use of the mobile phone as an information retrieval system nowadays has become a frequently performed task. Mobile phone that is easy and practical to carry anywhere, lightweight and with advanced technology makes the device more efficient to use than a desktop or a laptop. On these basis, we designed a simple application to recognize objects using the image histogram method for helping people especially to those affected by Alzheimer ,Aphasia, and those who are computer illiterate. This application is made using XCode with Objective-C programming language. The application is built in the iOS platform used on the mobile device technology company Apple, the iPhone. Key words Image Histogram, iOS, Xcode, Objective-C, Object, iPhone.